One Foot In, One Foot Out: Volunteer Motivation and Citizenship Practices in Paraíba’s Participatory Budgeting (REMUNOM, 2025)
Research on citizen participation in councils and participatory budgeting highlights the importance of volunteer work for keeping these arrangements alive, but there is still debate about which types of motivation actually help convert participation into more stable citizenship practices. This article examines the relationships between volunteer motivation and citizenship practices among councilors of Paraíba’s Participatory Budgeting Program (ODE-PB), comparing two cross-sectional studies conducted at equivalent stages of the participatory cycle: entry and end of the mandate. The study derives from a Master’s dissertation in Administration and brings together theoretical frameworks on volunteer motivation (Cavalcante, 2012, 2016) and citizenship practices (Caldas, 2020). Two independent datasets are used: (i) Leite’s (2023) database, with 245 councilors who served on ODE-PB regional councils between 2020 and 2022, representing entry into the mandate, and (ii) Silvestre’s (2024) database, with 200 councilors from a subsequent cycle, representing the end of the mandate. In both studies, validated scales of volunteer motivation and citizenship practices were applied, followed by confirmatory factor analysis and structural equation modeling estimated separately for each sample. The results show that value-expressive and understanding motives have stronger and more consistent associations with social and political citizenship practices than purely instrumental motives, especially among councilors at the end of their mandates. Affiliative and identity dimensions remain more sensitive to contextual and institutional features of ODE-PB. The study concludes that consolidating citizenship practices requires institutional arrangements capable of sustaining motivations oriented toward the common good and justice beyond immediate incentives, even though the datasets analyzed here do not track the same individuals over time.